New Paleomagnetic and Chronological Constraints on the Late Triassic Position of the Eastern Qiangtang Terrane: Implications for the Closure of the Paleo‐Jinshajiang Ocean. Issue 2 (18th January 2022) - Yu, Liang; Yan, Maodu; Domeier, Mathew; Guan, Chong; Shen, Miaomiao; Fu, Qiang; Xu, Wanlong; Xu, Zunbo; Niu, Zhichao; Yang, Liye; Shi, Rendeng; Zhang, Weilin; et al.
Abstract: The tectonic evolution of the Paleo‐Jinshajiang Ocean, and in particular the time of its closure, is debated. Here we present new constraints on the evolution of this region from an integrated paleomagnetic and geochronologic study of the Late Triassic Batang Group volcanic rocks in Qamdo, Eastern Qiangtang Terrane (EQT). Two zircon U‐Pb ages indicate that the volcanic rocks erupted at ∼227–222 Ma. New paleomagnetic results yield a robust Late Triassic paleopole of 57.6°N, 176.4°E ( A 95  = 7.8°), corresponding to a paleolatitude of 32.5 ± 7.8°N for the study area. Integrated with other lines of paleomagnetic and geological evidence, we show that the northward drift of the EQT placed it at the same paleolatitude as the Tarim Block by ∼227–222 Ma, which suggests that the Paleo‐Jinshajiang Ocean in the Qamdo region closed before that time, and likely around ∼230 Ma. Plain Language Summary: The closure of the Paleo‐Jinshajiang Ocean, which was one of the most important ancient oceans of Asia, closed when the Qiangtang Terrane (QT) collided with the terranes now located to the north of it. However, the evolution of this ocean, and especially the timing of its closure, are still debated. The drift history of the QT is a key to understanding the evolution of the Paleo‐Jinshajiang Ocean. We present here new constraints on the evolution of this region from an integrated paleomagnetic and zircon U‐Pb geochronologic study of Late Triassic volcanic rocks in Qamdo, Eastern QT. Two zircon U‐Pb geochronologic results indicate that the volcanic rocks erupted at ∼227–222 Ma. New paleomagnetic results yield a robust Late Triassic paleopole of 57.6°N and 176.4°E, and indicate that the study area was then located at a paleolatitude of 32.5 ± 7.8°N. In integrating these data with other lines of evidence, we show that a northward drift of the EQT since the early Permian brought it to the same paleolatitude as the Tarim Block by ∼227–222 Ma. This implies that the closure of the Paleo‐Jinshajiang Ocean in the Qamdo region occurred before 227–222 Ma, and likely around ∼230 Ma. Key Points: Volcanic rocks of the Late Triassic Batang Group are dated by U‐Pb on zircon to ∼227–222 Ma Paleomagnetic data from these rocks yield a robust Late Triassic paleopole of 57.6°N, 176.4°E(A95  = 7.8°) Closure of the Paleo‐Jinshajiang Ocean occurred before 227–222 Ma, and likely around ∼230 Ma